Kāmil al-taʿbīr. Volume 1 : Atharī jāmiʿ bih zabān-i Fārsī dar khābguzārī va taʿbīr-i rūyā, jild-i avval alif-shīn - Tiflīsī, Ḥubaysh b. Ibrāhīm (Miras Maktoob, ISBN: 9789004365452., 2019)
Since times immemorial man has been fascinated by his dreams. This is true of western civilization as it is true of any other civilization, including Islam. In the Qurʾān and the traditions, dreams and visions are frequently mentioned as instruments of divine guidance and instruction. This sanctification of the pre-existing oral tradition around dreams and their interpretation created room for this tradition to further develop, both in a religious and in a secular context. Dream interpretation remained unsystematized and mostly oral until Ḥunayn b. Isḥāq's (d. 260/873) Arabic translation of Artemidorus' (2nd cent. CE) Oneirocritica and Dīnawarī's al-Qādirī fi ʼl-taʿbīr (commissioned in 397/1006) that it inspired. From then onwards, a vast literature developed. The work published here is an important early text from the Persianate world, based on more than fifteen declared and other sources, most of which are lost. It is a compilatory work, with an introduction followed by an alphabetical inventory of themes. 2 vols; volume 1.